2017
DOI: 10.1140/epjc/s10052-017-5332-5
|View full text |Cite
|
Sign up to set email alerts
|

Traversable Schwarzschild-like wormholes

Abstract: In this paper we study relativistic static traversable wormhole solutions which are a slight generalization of Schwarzschild wormholes. In order to do this we assume a shape function with a linear dependence on the radial coordinate r . This linear shape function generates wormholes whose asymptotic spacetime is not flat: they are asymptotically locally flat, since in the asymptotic limit r → ∞ spacetimes exhibiting a solid angle deficit (or excess) are obtained. In particular, there exist wormholes which conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…: V,-vol of linear [33] as well as non-linear electrodynamics [34][35][36]. Moreover, wormhole solutions with other type of symmetries have been investigated in [37][38][39] and also the possibility to obtain a traversable Schwarzschild-like wormhole has been considered [40]. Furthermore, recently [41] was studied and analyzed the behavior of wormhole structures in the realm of dark matter profiles, dark matter Bose-Einstein condensates [42] and non-linear equation of state [43], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…: V,-vol of linear [33] as well as non-linear electrodynamics [34][35][36]. Moreover, wormhole solutions with other type of symmetries have been investigated in [37][38][39] and also the possibility to obtain a traversable Schwarzschild-like wormhole has been considered [40]. Furthermore, recently [41] was studied and analyzed the behavior of wormhole structures in the realm of dark matter profiles, dark matter Bose-Einstein condensates [42] and non-linear equation of state [43], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in Ref. [32] Cataldo et al studied a Schwarzschild-like traversable WH which is obtained by putting n = 1 with some slight modification. For geodesics, they showed that a test particle which is radially moving towards the throat always reaches it with zero velocity and at a finite time, while for radially outward geodesics the particle velocity tends to a maximum value, reaching infinity.…”
Section: Invariant Angle Methods Of Rindler and Ishakmentioning
confidence: 99%
“…It is interesting to examine whether a timelike or null geodesic can tunnel through the throat in the case Cataldo et al [32] studied, of the motion of test particles in the background of zero tidal force Schwarzschild-like WH spacetime. They showed that particles moving along the radial geodesics reach the throat with zero tidal velocity in finite time, while the particle velocity reaches maximum at infinity if it travels along a radially outward geodesic.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the parameter a is for the angular momentum of the wormhole. We also notice that the metric reduces to the one that describes a static Schwarzschild-like wormhole when a = 0 [15]. Thus, if we adopt the transformations indicated just above Eq.…”
Section: Static D-s Wormhole Versus Ellis Wormholementioning
confidence: 96%
“…Despite this, we can get other solutions with specific redshift functions without horizons [13,14]. An interesting generalization in this sense was carried out in [15] by taking a linear shape function, the so-called zero tilde Schwarzschild-like wormhole, which is static and traversable. Another wormhole based on Schwarzschild black hole solution was obtained by Damour and Solodukhin [16], upon modifying the time coefficient of the metric adding to it a very tiny positive constant.…”
Section: Introductionmentioning
confidence: 99%